THE EFFECT OF A SLOW RELEASE IMPLANT CONTAINING THE GnRH AGONIST DESLORELIN ON PITUITARY AND TESTICULAR FUNCTION IN MATURE MALE DOGS - Junaidi .; P.Williamson .; J.M. Cummins .; G.B. Martin .; T. Trigg . (Jurnal Sain Veteriner, 2000)
.